Efektivitas suplementasi kapsul daun kelor dalam meningkatkan kadar hemoglobin pada mahasiswi - Suhartini; Rusli Taher; Muliyana; Delfiani B.P; Reskiawati Azis; Ani; Abdul Thalib (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Anemia remains a prevalent public health issue, particularly among adolescent girls, due to increased iron needs and menstrual blood loss. Conventional iron supplements are often associated with side effects and low compliance. Moringa oleifera, known for its high content of iron, vitamin A, vitamin C, and protein, offers a promising natural alternative to improve hemoglobin levels. Purpose: This study aimed to investigate the impact of Moringa leaf capsule supplementation on hemoglobin levels in anemic female students at STIKES Graha Edukasi Makassar. Method: A quasi-experimental design with a one-group pretest-posttest approach was employed. Thirty female students diagnosed with anemia were selected using purposive sampling. Each participant was given Moringa leaf capsules (2 × 500 mg) daily for 14 consecutive days. Hemoglobin levels were measured before and after the intervention using a digital hemoglobinometer. Data were analyzed using the Wilcoxon Signed Rank Test. Results: Prior to the intervention, all participants were classified as anemic, with most in the moderate category. Following the 14-day supplementation, 90% of the students reached normal hemoglobin levels, while 10% remained in the mild anemia category. Statistical analysis revealed a significant difference in hemoglobin levels before and after the intervention (p < 0.0001), indicating that Moringa supplementation was effective. Conclusion: Supplementing with Moringa leaf capsules significantly improved hemoglobin levels in anemic female students. The synergy of iron, vitamins, and protein in Moringa supports hemoglobin synthesis and enhances iron absorption. Suggestions: Health professionals are encouraged to promote Moringa as a natural supplement for anemia prevention and treatment. Educational institutions should consider integrating local herbal-based nutrition programs. Further research with larger samples and extended durations is recommended to validate these findings.